1997
DOI: 10.1021/jp9626778
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ordered, Anisotropic Organic Monolayers on the Si(001) Surface

Abstract: It is shown that the SidSi dimers of the reconstructed Si(001) surface can react with the π bonds of unsaturated organic molecules to produce well-defined organic films with novel physical properties. Scanning tunneling microscopy (STM) studies show that the resulting layers are ordered both translationally and rotationally, with the SidSi dimers acting as a template for extending the translational and rotational order from the silicon substrate to the organic film. STM images and infrared spectroscopy experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
228
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(243 citation statements)
references
References 16 publications
13
228
1
1
Order By: Relevance
“…[1][2][3][4][5] Although many organic reactions on the Si(100)-2×1 surface have been examined, fewer have been explored on the Ge(100)-2×1 surface. Furthermore, although the set organic functional groups whose reactivity has been explored on semiconductor surfaces is now quite extensive, many organic functional groups are yet to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Although many organic reactions on the Si(100)-2×1 surface have been examined, fewer have been explored on the Ge(100)-2×1 surface. Furthermore, although the set organic functional groups whose reactivity has been explored on semiconductor surfaces is now quite extensive, many organic functional groups are yet to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 It has been demonstrated that ethylene reacts with the silicon surface via the interaction between the C-C double bond and silicon dimers, producing two Si-C bonds ͑the so-called di-bonding͒. Other alkenes are found to react in a similar fashion with the Si͑100͒ surface, [13][14][15][16][17] i.e., they bind to the surface also via the di-bonding configuration. Besides simple alkenes, conjugated dienes such as 1,3-butadiene and 1,3-cyclohexadiene have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The (2ϫ1) surface reconstruction obtained by a simple lateral translation of surface Si-atoms to form Si dimers was first suggested by Schlier and Farnsworth 2 in 1959 and further confirmed in the scanning tunneling microscopic ͑STM͒ studies by Hamers et al [3][4][5] Many of the physical and chemical properties of Si͑100͒ can be rationalized by considering a double bond feature of dimer, that is, a strong bond linking the two Si atoms and a rather weak bond. All studies of simple alkenes on Si͑100͒ have shown a facial ͓2ϩ2͔ cycloaddition reaction pathway; [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] despite the fact that, according to Woodward's rule, the analogous reaction of two organic alkenes is forbidden in the high-symmetry suprafacial-suprafacial ͓2 s ϩ2 s ͔ approach. 23 Moreover, experimental evidence has shown that the molecular stereochemistry is preserved through this reaction, thereby ruling out the suprafacialantarafacial ͓2 s ϩ2 a ͔ mechanism.…”
Section: Introductionmentioning
confidence: 99%